Effect of OH scavengers on the chemical composition of α-pinene secondary organic aerosol. Issue 1 (9th November 2022) - Bell, David M.; Pospisilova, Veronika; Lopez-Hilfiker, Felipe; Bertrand, Amelie; Xiao, Mao; Zhou, Xueqin; Huang, Wei; Wang, Dongyu S.; Lee, Chuan Ping; Dommen, Josef; Baltensperger, Urs; Prevot, Andre S. H.; et al.
Abstract : We present a detailed molecular characterization of SOA produced from α-pinene + O3 with a variety of OH scavengers. Radical chemistry controls the composition of SOA and scavengers alter these pathways and are incorporated into the SOA. Abstract : OH scavengers are extensively used in studies of secondary organic aerosol (SOA) because they create an idealized environment where only a single oxidation pathway is occurring. Here, we present a detailed molecular characterization of SOA produced from α-pinene + O3 with a variety of OH scavengers using the extractive electrospray time-of-flight mass spectrometer in our atmospheric simulation chamber, which is complemented by characterizing the gas phase composition in flow reactor experiments. Under our experimental conditions, radical chemistry largely controls the composition of SOA. Besides playing their desired role in suppressing the reaction of α-pinene with OH, OH scavengers alter the reaction pathways of radicals produced from α-pinene + O3 . This involves changing the HO2  : RO2 ratio, the identity of the RO2 radicals present, and the RO2 major sinks. As a result, the use of the OH scavengers has significant effects on the composition of SOA, including inclusions of scavenger molecules in SOA, the promotion of fragmentation reactions, and depletion of dimers formed via α-pinene RO2 –RO2 reactions. To date fragmentation reactions and inclusion of OH scavenger products into secondary organic aerosol have not been reported in atmospheric simulation chamber studies. Therefore, care should be considered if and when to use an OH scavenger during experiments.